Qualitätsmanagement auf der Intensivstation - Riessen, Reimer; Haap, Michael (DMW - Deutsche Medizinische Wochenschrift, 2018)
The care of critically ill patients in an intensive care unit is effected by an interprofessional and interdisciplinary team. Quality and success of intensive care is mainly based on the performance of this team. Suitable quality management measures, based on valid indicators, insure an optimal workflow for the benefit of patient safety.
Keywords: Qualitätsmanagement; Struktur; Ergebnis; Prozess; Personal; peer-review